Development of a novel estimation method for hemoglobin A1c using glycated albumin in type 2 diabetes mellitus patients with end-stage renal disease - Nakamura, Akihiko; Kodera, Ryo; Sakamoto, Noriko; Ujike, Haruyo; Wada, Jun; Shikata, Kenichi; Makino, Hirofumi (Diabetology international, 2018)
Aim We developed a novel estimation method for hemoglobin A1c (HbA1c) in type 2 diabetes (T2D) patients with end-stage renal disease (ESRD). This method is based on the glycated albumin (GA) level. Methods Of the 788 Japanese patients with T2D included in this study, 545 had normal renal function (NRF group) and 243 had ESRD. Oral glucose tolerance tests (OGTTs) were performed in 80 subjects. The variables GA, body mass index (BMI), hemoglobin (Hb), and estimated glomerular filtration rate (eGFR) were significantly associated with the GA-to-HbA1c ratio and were used to determine the estimated HbA1c (eHbA1c). One method of estimating HbA1c involved dividing GA by the GA-to-HbA1c ratio predicted from the estimated regression equation; the estimated HbA1c obtained in this manner was denoted eHbA1c-1. Results eHbA1c-1 (%) = GA × [4.688 − 18.833 × GA −1 − 0.015 × BMI − 0.037 × Hb (− 0.002 × eGFR for patients without ESRD)] −1 ; adjusted R 2 = 0.676 for actual HbA1c. The sensitivity of eHbA1c-1 was better than that of GA for diabetes diagnosis using the 75-g OGTT. There were no differences in the slope of eHbA1c-1 versus GA and the variance of eHbA1c-1 between the ESRD and NRF groups. eHbA1c-1 was not associated with Hb, erythropoiesis-stimulating agent use, or ESRD concomitance. Conclusions eHbA1c-1 may be a useful parameter for estimating HbA1c in T2D patients with ESRD.